PELAKSANAAN PENDELEGASIAN WEWENANG BUPATI KEPADA CAMAT DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH - Riko Eka Kusuma (Universitas Airlangga, 2016)
AbstractSince the enactment of Law No. 12 Year 2008 on the second Amendment to the Law Number 32 Year 2004 on Regional Government, as an interpretation of Article 18 , to bring new changes in governance in the region. This law has fundamentally changed the practices of government, one of which is related to the position, duties and functions of the District. The main changes was in the definition of the township itself besides the other changes such as the shape of the organization, financing, personnel appointments, logistics fulfillments and accountability,. Previously, the District was an administrative region in the context of the work environment that organizes the implementation of tasks in the area of public administration. While according to the Law No. 12 of 2008, Article 126 Section 3, the District is the district/city in the context of the principle of decentralization. That is, if used within the framework of the principle of deconcentration district, it is one of the administrative area, in addition to national, provincial, district and municipality, as well as administrative city. At the present time the Districts is the working area of the districts of the region. However, districts are not a territory, it is a service areas.Keywords: Delegation of authority, Head of District, Regional Government